Pemberdayaan Masyarakat Perum Deppen, Klodokan, Depok, Sleman, Yogyakarta Program Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) - Dyah Rosiana Puspitasari; Ian Ramadhan Yamin; Raihan Hairansyah (Universitas 45 Surabaya, 2023)
One of the problems in the Micro, Small and Medium Enterprises (UMKM) sector of Perum Deppen, Kledokan Village, Depok District, Sleman Regency, Special Region of Yogyakarta is a marketing problem and UMKM do not have a product identity which makes people less interested in the food products they sell. offer. The method used in this community service research is a participatory observation method, which involves researchers directly involved in community activities that are being empowered. Researchers observe and participate in daily activities, interact with community members, and record their experiences and observations. This Participatory Observation Method method provides direct insight into the dynamics and processes of empowerment that occur, and the programs implemented in UMKM. The program that is needed by the community is to create an Instagram account and create a logo or product identity. The results of this UMKM Development program are that it can improve marketing and make it easier for UMKM s to promote their products to reach a wider market and be able to compete with existing UMKM products.